2014
DOI: 10.1038/eye.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

Foldable vs rigid lenses after phacoemulsification for cataract surgery: a randomised controlled trial

Abstract: Purpose To compare the outcomes of phacoemulsification with either a 2.5-mm clear corneal incision and a foldable intraocular lens (IOL) or a 5-mm sclerocorneal tunnel incision and a rigid polymethyl methacrylate (PMMA) IOL. Methods In a prospective, randomised clinical trial of phacoemulsification cataract surgery, 1200 patients received either a foldable hydrophilic acrylic IOL through a 2.5-mm corneal incision or an inexpensive rigid PMMA IOL via a 5-mm sclerocorneal tunnel. Intra-and post-operative data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…7 In another study by Hennig et al, PCO rate was 23.3% in acrylic and 36.1% in PMMA groups at the end of one year. 8 Hazra et al found that there was no difference in PCO formation between the rigid and foldable lens designs. 9 According to Takkar et al, significant PCO is associated with PMMA IOLs.…”
Section: Discussionmentioning
confidence: 98%
“…7 In another study by Hennig et al, PCO rate was 23.3% in acrylic and 36.1% in PMMA groups at the end of one year. 8 Hazra et al found that there was no difference in PCO formation between the rigid and foldable lens designs. 9 According to Takkar et al, significant PCO is associated with PMMA IOLs.…”
Section: Discussionmentioning
confidence: 98%
“…While dogs have an amplified uveal inflammatory response to surgery compared to that seen in humans, one would otherwise expect dogs to have a similarly improved outcome with a small incision and foldable lenses. On the other hand, a recent randomized clinical trial comparing foldable vs. rigid IOLs in people found an excellent visual outcome in both groups (>90% with uncorrected visual acuity of 6/18 or better), although PCO was more common in the PMMA group as compared to the foldable IOL group (36.1% vs. 23.3%) . One recent veterinary study found that the PCO score via direct slit lamp was significantly lower for acrylic foldable IOLs when compared to PMMA IOLs in a group of dogs .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Nepal by Hennig A et al, [14] compared the results of phacoemulsification done using foldable versus rigid IOL's, in which the foldable lens was inserted using a 2.5mm clear corneal incision, while the rigid lens was inserted using a 5mm sclerocorneal incision. They found no significant difference in the visual outcome of phacoemulisfication using either a rigid intraocular lens (PMMA PC IOL) or a foldable PC IOL (hydrophilic acrylic).…”
Section: Discussionmentioning
confidence: 99%